Environmental and governance strategies in ESG for industry 4.0: A systematic review - Hammad, Muhammad Yahya; Syed Radzi, Rahamaddulla; Muhammad Ashraf, Fauzi (AIMS Press, 2025)
This study examined the integration of Industry 4.0 technologies with environmental, social, and governance (ESG) strategies to improve organizational sustainability and competitiveness. Industry 4.0 technologies, including blockchain, artificial intelligence (AI), the Internet of Things (IoT), and big data analytics, offer transformative capabilities for ESG reporting, resource optimization, and operational efficiency. By addressing sustainability challenges and advancing governance practices, these technologies enable businesses to meet their environmental and governance responsibilities while achieving economic growth. However, implementing Industry 4.0 in ESG frameworks presents challenges, such as high costs, poor data quality, and resistance to change. This paper analyzed existing literature to identify opportunities and barriers to aligning ESG with Industry 4.0, providing insights for managers, researchers, and policymakers. The report adds to the body of knowledge on sustainable innovation by pointing out the advantages and disadvantages of this integration. It also provides a roadmap for achieving sustainability-implementing goals over the long run in a rapidly evolving digital landscape.